FlashCam: A fully digital camera for the Cherenkov telescope array medium-sized telescopes - Pühlhofer, G.; Barcelo, M.; Bauer, C.; Bi, B.; Catalano, Jacqueline; Diebold, S.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
FlashCam is an innovative camera designed for the focal plane instrumentation of Cherenkov telescopes. The concept of the FlashCam trigger and readout system is based on the continuous digitization and digital processing of the photo detector signals on FPGAs, and on a high performance, Ethernet-based front-end readout. Because of the modular design, the electronics that have been developed can serve either photomultiplier tubes or silicon-based photon detectors. In the framework of the CTA (Cherenkov telescope array) project, the FlashCam team has developed a PMT-based camera that is suitable for the medium-sized telescopes. With over 100 Cherenkov telescopes, the CTA observatory will run the most sensitive ground-based telescope systems for TeV gamma-ray astronomy when the two arrays in the Northern and Southern Hemisphere (with three different telescope sizes) will go into operation in the upcoming years.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Cherenkov Telescope Array; electronics; gamma-rays; Imaging Atmospheric Cherenkov Telescopes

Performance of the New FlashCam-based Camera in the 28 m Telescope of H.E.S.S. - Bi, Baiyang; Barcelo, Miquel; Bauer, Christian; Benkhali, Faical Ait; Catalano, Jacqueline; Diebold, Sebastian; Föhr, Christian; Funk, Stefan; Giavitto, Gianluca; Hermann, German; Hinton, Jim; Jung-Richardt, Ira; et al. (Proceedings of 37th International Cosmic Ray Conference — PoS(ICRC2021), 2022)
In October 2019, the central 28 m telescope of the H.E.S.S. experiment has been upgraded with a new camera. The camera is based on the FlashCam design which has been developed in view of a possible future implementation in the Medium-Sized Telescopes of the Cherenkov Telescope Array (CTA), with emphasis on cost and performance optimization and on reliability. The fully digital design of the trigger and readout system makes it possible to operate the camera at high event rates and to precisely adjust and understand the trigger system. The novel design of the frontend electronics achieves a dynamic range of over 3,000 photoelectrons with only one electronics readout circuit per pixel. Here we report on the performance parameters of the camera obtained during the first year of operation in the field, including operational stability and optimization of calibration algorithms.
CRIS-Team Scopus Importer:2024-12-16

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

Readout electronics testing during mass production of FlashCam cameras for the Cherenkov Telescope Array - Diebold, S.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Capasso, M.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; et al. (OPTICS FOR EUV, X-RAY, AND GAMMA-RAY ASTRONOMY VIII, 2017)
CRIS-Team WoS Importer:2020-01-15

Trigger performance verification of the FlashCam prototype camera - Sailer, S.; Werner, F.; Hermann, G.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Canelli, F.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
FlashCam is a camera proposed for the medium-sized telescopes of the Cherenkov Telescope Array (CTA). We compare camera trigger rates obtained from measurements with the camera prototype in the laboratory and Monte Carlo simulations, when scanning the parameter space of the fully-digital trigger logic and the intensity of a continuous light source mimicking the night sky background (NSB) during on-site operation. The comparisons of the measured data results to the Monte Carlo simulations are used to verify the FlashCam trigger logic and the expected trigger performance.
CRIS-Team Scopus Importer:2019-06-25
Keywords: CTA; DAQ; Data management; FlashCam; Front end; Trigger